Measuring Hazards of Undetectable Viral Load among Hepatitis C Antibody Positive Residents of a Large Southern California County. (November 2021) - Goodman, Sara; Zahn, Matthew; Bruckner, Tim; Boden-Albala, Bernadette; Lakon, Cynthia M.
Abstract Background Hepatitis C virus (HCV) infection is the most common bloodborne infection in the U.S. However, only a small proportion of persons are treated and cured. Previous research has not characterized sociodemographic characteristics of who receives treatment. We examined predictors of undetectable for HCV in Orange County, the sixth largest county in the United States, where HCV is the most commonly reported infection. Methods: From 2014 to 2020, we acquired public health surveillance data from 91, 165 HCV antibody-positive care encounters from the California Reportable Disease Information Exchange (CalREDIE). We used a time-to-event proportional hazards framework to estimate individual and area-level correlates of time-to-HCV undetectable viral load among HCV + individuals. Results: Older adults (>65 years) showed an increased hazard of undetectable viral load relative to younger adults (HR = 2.00). In addition, residents of census tracts with greater enrollment in health insurance showed a greater likelihood of undetectable viral load (HR = 1.36). The moderating effect of higher tract median household income and higher tract levels of health insurance were more likely to have undetectable viral load and was statistically significant. Conclusion: In a large urban county, HCV antibody-positive older adults appear much more likely to show undetectable viral load compared to younger adults. Residents in areas with higher quartiles of health insurance enrollment have an increased likelihood of undetectable viral load. The extent to which constraints impede HCV care requires further investigation, including follow-up studies on health insurance type to test the relationship of health insurance type to undetectable viral load.